Standardization and Quality Control of Siddha Herbo-Mineral Formulation Siva Nama Rasam (SNR) - Antonyraj, Kiruba Annammal Paul Abraham; Shanthirappan, Suresh Ramasamy, Sivakkumar (Asian Journal of Biological and Life Sciences, 2025)
Background: The fundamental causes of ailments could be more effectively and efficiently treated with siddha medications. Standardising herbal formulations is a key step towards assuring pharmaceutical reliability and efficacy. Siva Nama Rasam is a traditional siddha Herbo mineral preparation. This formulation was stated in Anuboga Vaithiya Navaneedham, suggested for Iraippirumal (Bronchial asthma), Kurainoi (Leprosy), Sanni (Delirium), Moolanoi (Haemorrhoids), Sayam (Tuberculosis), and other forms of valippu noi (Epilepsy). Objectives: The purpose of this study is to create a standard for Siva Nama Rasam (SNR) in accordance with PLIM (Pharmacopeia Laboratory of Indian Medicine) guidelines. Materials and Methods: Four of the six chemicals that make up the preparation are inorganic, while the other two are substances derived from plants. The recognizable proof of different substance constituents is identified by HPTLC test. Along with this organoleptic character, physico-chemical parameters, solubility profile, confirmatory specification, particle size determination and heavy metal analysis were additionally done for the prepared medicine. Conclusion: The results obtained can be considered viable for this preparation.
Keywords: Herbo-Mineral Medicine; HPTLC; Physiochemical analysis; PLIM Guidelines; SNR